Ex Vivo Heart Perfusion for Cardiac Transplantation Allowing for Prolonged Perfusion Time and Extension of Distance Traveled for Procurement of Donor Hearts: An Initial Experience in the United States. Issue 3 (22nd February 2023) - Isath, Ameesh; Ohira, Suguru; Levine, Avi; Pan, Stephen; Aggarwal-Gupta, Chhaya; Lanier, Gregg M.; Wolfe, Kevin; Spielvogel, David; Gass, Alan; Kai, Masashi
Abstract : Background: Scarcity of donor hearts continues to be a challenge for heart transplantation (HT). The recently Food and Drug Administration–approved Organ Care System (OCS; Heart, TransMedics) for ex vivo organ perfusion enables extension of ex situ intervals and thus may expand the donor pool. Because postapproval real-world outcomes of OCS in HT are lacking, we report our initial experience. Methods: We retrospectively reviewed consecutive patients who received HT at our institution in the post–Food and Drug Administration approval period from May 1 to October 15, 2022. Patients were divided into 2 groups: OCS versus conventional technique. Baseline characteristics and outcomes were compared. Results: A total of 21 patients received HT during this period, 8 using OCS and 13 conventional techniques. All hearts were from donation after brain death donors. The indication for OCS was an expected ischemic time of >4 h. Baseline characteristics in the 2 groups were comparable. The mean distance traveled for heart recovery was significantly higher in the OCS group (OCS, 845 ± 337, versus conventional, 186 ± 188 mi; P < 0.001), as was the mean total preservation time (6.5 ± 0.7 versus 2.5 ± 0.7 h; P < 0.001). The mean OCS time was 5.1 ± 0.7 h. In-hospital survival in the OCS group was 100% compared with 92.3% in the conventional group ( P = 0.32). Primary graft dysfunction was similar in both groups (OCS 12.5% versus conventional 15.4%; P = 0.85). No patient in the OCS group required venoarterial extracorporeal membrane oxygenation support after transplant compared with 1 in the conventional group (0% versus 7.7%; P = 0.32). The mean intensive care unit length of stay after transplant was comparable. Conclusions: OCS allowed utilization of donors from extended distances that otherwise would not be considered because ischemic time would be prohibitive by conventional technique.